2010
DOI: 10.1016/j.amjcard.2010.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Significance of Exercise-Induced Left Ventricular Outflow Tract Pressure Gradients in Hypertrophic Cardiomyopathy

Abstract: The relation of exercise-induced left ventricular (LV) outflow tract obstruction to functional capacity in hypertrophic cardiomyopathy (HC) is incompletely defined. Thus, we assessed the patterns of onset of physiologically provoked LV outflow gradients and exercise performance in 74 consecutive patients with HC (age 45 ± 16 years; 74% men) without LV outflow obstruction at rest. The subaortic gradients were measured serially using echocardiography in these 74 patients during maximum, symptom-limited, upright … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 32 publications
0
16
1
4
Order By: Relevance
“…In contrast, when simultaneous echocardiographic imaging was performed on patients who underwent upright stationary bicycle testing, there was a very high correlation between the provocable LVOT gradient obtained during peak upright exercise and the LVOT gradient in the immediate postexercise supine position. 36 Other relevant studies of upright bicycle exercise involving patients with HCM are summarized in Table 1. 37,38 There are caveats to mention when evaluating patients for exercise-induced LVOTobstruction, regardless of the type of exercise.…”
Section: Methods Of Inducing Left Ventricular Outflow Tract Obstructimentioning
confidence: 99%
“…In contrast, when simultaneous echocardiographic imaging was performed on patients who underwent upright stationary bicycle testing, there was a very high correlation between the provocable LVOT gradient obtained during peak upright exercise and the LVOT gradient in the immediate postexercise supine position. 36 Other relevant studies of upright bicycle exercise involving patients with HCM are summarized in Table 1. 37,38 There are caveats to mention when evaluating patients for exercise-induced LVOTobstruction, regardless of the type of exercise.…”
Section: Methods Of Inducing Left Ventricular Outflow Tract Obstructimentioning
confidence: 99%
“…The incidence and severity of exercise-induced LVOT can be increased in post-prandial tests (63) . A study has demonstrated that early development of obstruction is associated with higher reduction in the function capacity (64) . Another study has shown a progressive increase in the LVOT gradient by a range of physiologic manoeuvres: from standing to Valsalva to exercise (65) .…”
Section: Lvot Obstructionmentioning
confidence: 99%
“…Consecutive measurements under baseline conditions in supine and orthostatic position, and after, at the peak of the exercise and on the recovery phase in orthostatism showed a continuous elevation of the gradient 45 . In a later study, the peak of exercise gradient was demonstrated to present correlation with that on the supine recovery phase, and that the early development of obstruction was associated to higher reduction of function capacity 46 . In other set of cases, although elevation of gradient in 76% of the patients in standing position has been observed, a higher increment was found in exertion, in measurements made in supine recovery phase 40 .…”
Section: The Valsalva Maneuver Increases or Induces Sam (mentioning
confidence: 99%